FRASE “BENCANA KARENA MUSLIHAT DAN KHIANAT” SEBAGAI PENANDA UTAMA PADA DRAMA HAMLET, PRINCE OF DENMARK KARYA WILLIAM SHAKESPEARE (SEBUAH KAJIAN SEMIOTIK) - Anggarani Wilujeng (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
The objective of this writing is to reveal and show the phrase of “lest more mischief, including plots and errors” as a primary signifier in the drama of William Shakespeare’s Hamlet, Prince of Denmark using semiotics approach. By using semiotics approach, in the text, the writer can find a primary signifier of the phrase of “lest more mischief, including plots and errors” through the signs and type; the index, resulting in the overall meaning of the text.